Interpregnancy intervals and adverse birth outcomes in high-income countries: An international cohort study. - Gizachew A Tessema; M Luke Marinovich; Siri E Håberg; Mika Gissler; Jonathan A Mayo; Natasha Nassar; Stephen Ball; Ana Pilar Betrán; Amanuel T Gebremedhin; Nick de Klerk; Maria C Magnus; Cicely Marston; et al. (PLoS ONE)
Background Most evidence for interpregnancy interval (IPI) and adverse birth outcomes come from studies that are prone to incomplete control for confounders that vary between women. Comparing pregnancies to the same women can address this issue. Methods We conducted an international longitudinal cohort study of 5,521,211 births to 3,849,193 women from Australia (1980-2016), Finland (1987-2017), Norway (1980-2016) and the United States (California) (1991-2012). IPI was calculated based on the time difference between two dates-the date of birth of the first pregnancy and the date of conception of the next (index) pregnancy. We estimated associations between IPI and preterm birth (PTB), spontaneous PTB, and small-for-gestational age births (SGA) using logistic regression (between-women analyses). We also used conditional logistic regression comparing IPIs and birth outcomes in the same women (within-women analyses). Random effects meta-analysis was used to calculate pooled adjusted odds ratios (aOR). Results Compared to an IPI of 18-23 months, there was insufficient evidence for an association between IPI <6 months and overall PTB (aOR 1.08, 95% CI 0.99-1.18) and SGA (aOR 0.99, 95% CI 0.81-1.19), but increased odds of spontaneous PTB (aOR 1.38, 95% CI 1.21-1.57) in the within-women analysis. We observed elevated odds of all birth outcomes associated with IPI ≥60 months. In comparison, between-women analyses showed elevated odds of adverse birth outcomes for <12 month and >24 month IPIs. Conclusions We found consistently elevated odds of adverse birth outcomes following long IPIs. IPI shorter than 6 months were associated with elevated risk of spontaneous PTB, but there was insufficient evidence for increased risk of other adverse birth outcomes. Current recommendations of waiting at least 24 months to conceive after a previous pregnancy, may be unnecessarily long in high-income countries.